(untitled) (Tanzania Medical Journal, 2021)
Background Majority of children with cancer live in low- and middle-income countries. The data is scarce on the epidemiology of childhood cancer in these countries. In this study, we enrolled children and adolescents with cancer at the only cancer hospital in Tanzania and determined the epidemiology and HIV infection among this population. Methodology This was a descriptive hospital-based study conducted at Ocean Road Cancer Institute in Dar es salaam, Tanzania. Data were collected for eight months (May to December 2010). Participants were enrolled consecutively as they presented to the hospital. Demographic data, HIV status and clinical diagnosis were determined and recorded. Each patient was followed up until a final diagnosis was reached, and investigations for disease staging were completed. Results One hundred and fifty-one (151) patients were enrolled in the study. Mean age at presentation was 5.8 years (range 3-17years), and 51.7% of participants were males. Sixty-three per cent (63%) of patients had their diagnoses confirmed by histology or cytology. Retinoblastoma was the most common malignancy (29.1%) followed by Nephroblastoma (11.3%), Burkitt lymphoma (10.6%) and Acute Lymphoblastic Leukemias (10.6%). More than half (58.2%) of patients aged three years or younger had Retinoblastoma. Four patients (2.8%) had HIV infection; three of them with Kaposi’s sarcoma and one with Burkitt lymphoma. Conclusion Retinoblastoma was the most typical malignancy followed by Wilms tumour, Burkitt lymphoma and acute lymphoblastic leukaemia. The prevalence of HIV infection was very low among patients with the described malignancies. Key Words: Childhood Malignancies, Tanzania.